IDENTIFIKASI PELAKSANAAN TUGAS PERAWATAN KESEHAAN KELUARGA DENGAN HIPERTENSI - Agustina " "; Ari Pristiana Dewi; Yesi " Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Hypertension is an abnormal high blood pressure measurable three occasion in different chance. Family health care tasks is an obligation that should be performed by a family in order to optimize the health of the family members. The role of the family is very significant in caring and assisting with the hypertension patient. The purpose of this research is to Identify the implementation of family health care tasks with hypertension patient in the working area of Simpang Baru Public Health Center. The design of this research was descriptive. The total sample are 40 family member who were taken by using cluster sampling techniques. The instrument used was a questionnaire that has been tested its valid and reliable. The tested results showed that the number of family could not identify problems (70%), families member making decision (55%), caring for member of family (65%), families member modifying the environment (62,5%), families member utilizing the health facilities (72,5%). The conclusion of this research the implementation of family health care tasks with hypertension patient in the working area of Simpang Baru Public Health Center the most of were capable.  Keyword :  the implementation of family health care tasks, the family member with hypertension patient